Willingness to use e-government services in Ministry Of Higher Education Malaysia / Amilatul Azwa Kamaruzaman - Kamaruzaman, Amilatul Azwa (Faculty of Business and Management, 2017)
The purpose of this study was to determine the factor that affecting the willingness to use e-government services in Ministry of Higher Education Malaysia. There are four variables that was highlighted in this study which are security and privacy, human computer literate and website design. There are 169 respondents that were the employers and employees of Ministry of Higher Education Malaysia. The finding showed that only two variables are significant which are security and privacy and website design. Thus, these variables consider the factors that affecting willingness to use e-government services. Meanwhile there are another two variables that showed negative relationship on willingness to use e-government services which are human computer literate and website design. This study used primary data and also secondary data for supporting the sampling technique. Questionnaire was used to collect all the data from the respondents in accomplishing the research objectives. Next, the data for this study was analysed using multiple statistical procedures: mean point value, standard deviation, and correlation analysis. The result of this study presented showed that security and privacy, human computer literate, infrastructural and website design are the factors that affect willingness to use e-government services. This study can be seen as a foreword to a more detailed study to be carrying by future research on willingness to use e-government services in Malaysia.